Biomass accumulation and growth curve in sugarcane fertigated with nitrogen doses - Kölln, Oriel Tiago; de Castro Gava, Glauber José; Mariano, Eduardo; Cantarella, Heitor; Panutti, Luiz Eduardo [UNESP]; Uribe, Raul Martinez; Arlanch, Adolfo Bergamo [UNESP]; Paludetto, Alexandre; Pereira, Catarinie Diniz; Trivelin, Paulo Cesar Ocheuze (Southern Cross Publishing, 2023)
This study aimed to evaluate the growth curve, biomass and N accumulation in aboveground sugarcane as a function of nitrogen doses applied by subsurface drip irrigation during the crop growth cycle. The experiment was developed under field conditions Jau city, São Paulo state, Brazil. The treatments were four nitrogen doses – namely 50, 100, 150 and 200 kg ha-1 N – in urea form, in addition to a control treatment (without N), with completely randomized block and four repetitions. The N doses were applied gradually by subsurface drip irrigation spread throughout the sugarcane crop cycle. Biometrics and physiologic parameters and biomass accumulation were evaluated at five sampling times. Linear and quadratic responses of these parameters were verified as a function of N application. Elevating the N dose from 100 to 200 kg ha-1 increased the biomass and the N accumulation of sugarcane above ground by 20 Mg ha-1 and 95 kg ha-1, respectively. The nitrogen fertilization applied by subsurface drip irrigation increased the biomass and N accumulation of aboveground sugarcane, as well as the production rate of all parameters. The gap between maximum biomass accumulation rate (BAR) and nitrogen accumulation rate (NAR) was smooth due drip irrigation management. The irrigation management combined with better plant nutrition show highest results to biomass production.
Keywords: plant nutrition; Saccharum spp; subsurface drip irrigation; water management